The Value of Buy‐Online‐and‐Pickup‐in‐Store in Omni‐Channel: Evidence from Customer Usage Data. Issue 4 (24th January 2020) - Song, Peijian; Wang, Quansheng; Liu, Hefu; Li, Qi
Abstract : The buy‐online‐and‐pickup‐in‐store (BOPS) service has been widely treated by retailers as an important omni‐channel initiative. However, few studies have attempted to quantify the impact of BOPS usage on subsequent purchase behaviors or examine the critical roles of offline stores in the value generation of BOPS. Thus, through 25, 724 BOPS instances used by 16, 202 unique customers via a hybrid retailer, this study investigated the impact of customers' BOPS usage on their online and offline purchase frequency and purchase amount. The moderating effect of offline store factors was investigated based on data from a focal retailer consisting of 110 stores in four cities. Using a combination of propensity score matching and difference‐in‐difference (DID) identification, our research found the significant positive effects of BOPS usage on offline purchase frequency and online purchase amount. We also found nuanced moderating effects of offline store characteristics (i.e., store density, product variety, and competition intensity) in the influence of BOPS usage on purchase behaviors. Our study thus generates important theoretical and practical implications for omni‐channel operations.